Multichannel WDM vibrometry at 1550 nm - Waz, Adam Tomasz; Dudzik, Grzegorz; Kaczmarek, Pawel Roman; Abramski, Krzysztof Marek (Photonics Letters of Poland, 2014)
We present a multichannel laser-fiber vibrometer concept, realization and obtained results. The vibrometer is based on the WDM (Wavelength Division Multiplexing) telecommunication technique and operates at 1550 nm region. Four independent fibre-coupled laser diodes form a system of sources for multipoint vibration measurement according to the rule "one wavelength-one point". Such solution minimize crosstalk between channels and allows to arrange a measuring points freely. Our system measure vibrations at four points simultaneously. It allows to phase-relation measurements between vibrating points. Additionally it is all fiber design thus it gives possibility to measure vibrations in hard to reach places. Full Text: PDF References G. D'Emilia "Evoluation of measurement characteristics of a laser Doppler vibrometer with fiber optics components" SPIE 2358 (1994). CrossRef D. Egan et al. "A polarization-based optical fibre vibrometer" Meas. Sci. Technol. 8, 3 (1997). CrossRef M. Bauer et al. "High-precision laser vibrometers based on digital Doppler-signal processing" Proc. SPIE 4827 (2002). CrossRef X. Li et al. "Reflectivity and illuminating power compensation for optical fibre vibrometer" Meas. Sci. Technol. 15, 9 (2004). CrossRef W. MacPherson et al." Multipoint laser vibrometer for modal analysis", Applied Optics, 46,16 (2007). CrossRef J. Buytaert et al. "Indentation measurements on the eardrum with automated projection moiré profilometry" Optics and Lasers in Engineering, 47, 3(2009). CrossRef H. Van Elburg et al. "High-resolution quadruple-channel heterodyne laser velocimeter based on birefringent optics" Optik - International Journal for Light and Electron Optics, 119, 10 (2008). CrossRef Polytec GmBH Waldbronn, Germany, Fibre Optic Laser Vibrometer technical Data Sheets, http://www.polytec.com MetroLaser, Inc. http://www.metrolaserinc.com A. Waz et al. "WDM optocommunication technology used for multipoint vibrometry" Proc. SPIE 7098, (2008). CrossRef A. Waz et al. "Laser-fibre vibrometry at 1550 nm", Meas. Sci. Tech. 20, (2009). CrossRef P. Kaczmarek et al. "Laser Doppler vibrometry with acoustooptic frequency shift" Opt. Appl. 34, 3 (2004). DirectLink A. Waz et al. "Recent development of WDM fiber vibrometry", AIP Conf. Proc. 1457, 227 (2012). CrossRef